Sakinah Mawadah and Rahmah in QS. al-RÅ«m [30]: 21: Analysis of QirÄah MubÄdalah Faqihuddin Abdul Kodir (L.1971) - Bunda, Mutiara Fitri Cahya; Nafisah, Mamluatun (AJIS: Academic Journal of Islamic Studies, 2024)
The phenomenon of divorce in Indonesia increases every year with various problems faced in a family. As time goes by, problems and solutions to overcome these problems also change, so that solutions that were commonly used in the past to deal with current household disputes are not appropriate. If referring to the interpretation of QS. al-RÅ«m [30]: 21 does not yet fully contain an interpretation regarding the current phenomenon of the concepts of sakinah mawadah and rahmah. This paper tries to respond to this problem by analyzing the interpretation of the QS. al-RÅ«m [30]: 21 uses the QirÄ'ah MubÄdalah perspective. The results of this research include; First, the interpretation of QS. al-RÅ«m [30]: 21 in the perspective of mubÄdalah is Allah SWT. shows one of the signs of His greatness by creating for his servants couples (both husband and wife) of the same kind so that they both feel calm and at ease, and tend to each partner. Then, to obtain this calm and tranquility, Allah SWT. bring a sense of love and affection between the two. These are the signs of His greatness for a people who think. Second, in its literal pronunciation, the verse discusses men who obtain peace from their wives, but in terms of its meaning, this verse also applies to women who obtain peace from their husbands. This is emphasized in the phrase bainakum which shows the reciprocal meaning between husband and wife.